2010
DOI: 10.1088/0953-4075/43/6/065204
|View full text |Cite
|
Sign up to set email alerts
|

EUV emission spectra in collisions of multiply charged Sn ions with He and Xe

Abstract: Extreme ultraviolet emission spectra of multiply charged Sn ions were measured in the wavelength range 5-38 nm, following electron capture into the excited states of slow Sn q+ (q = 5-21) ions passing through He and Xe gas targets. Identification of the transitions was carried out by comparison with calculations using the Hebrew University Livermore Laboratory Atomic physics Code. The target and the charge-state dependences of 4d-n (n = 4f, 5p and 5f) and 4p-4d transitions were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 27 publications
(43 reference statements)
2
33
0
Order By: Relevance
“…In the case of Sn and Xe ions, the calculated wavelength of the 4p −4d +4d −4f transition array is slightly different from that obtained experimentally because of the effect of CI. 10,13 In the case of Tb, we observe the best agreement between the calculation and experiment at T e =80 eV and after shifting the calculated spectrum by Ϫ0.15 nm.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In the case of Sn and Xe ions, the calculated wavelength of the 4p −4d +4d −4f transition array is slightly different from that obtained experimentally because of the effect of CI. 10,13 In the case of Tb, we observe the best agreement between the calculation and experiment at T e =80 eV and after shifting the calculated spectrum by Ϫ0.15 nm.…”
mentioning
confidence: 52%
“…The model reproduced the emission spectrum after correction of line wavelengths based on detailed spectroscopic measurements. 10,11 Furthermore, the model was combined with the power balance model 12 to calculate and optimize the conversion efficiency ͑CE͒ of a laser-produced plasma source, the results of which showed that a high CE could be obtained using a CO 2 laser pumped Sn microdroplet target.…”
mentioning
confidence: 99%
“…It should be emphasized that the lines from Ga-and Ge-like tin were identified for the first time in this work. The identifications of Zn-like and Ga-like tin ions have also been validated by spectra obtained in the charge exchange collisions experiment [21], and also by analyses of temporal variations of line intensities in the discharge. Though the calculated wavelengths for Ga and Ge-like tin lines are systematically shifted by longer wavelength in comparison with the measured ones, it can be attributed to an overestimation in Slater Condon parameters and the lack of scaling of the spin-orbit integrals in the calculation.…”
Section: Analysesmentioning
confidence: 85%
“…In this study, assignments of the strong discrete lines from tin and xenon ions, and the complicated broad features of tungsten ions have been performed with the help of comparisons with the previous experimental results, the experimental spectra in charge exchange collisions [21] and the theoretical calculations by Cowan code. Consequently, most of the strong discrete lines in longer wavelength side of the UTAs from tin and xenon have been assigned to the 4p-4d or 4d-4f transitions of higher charge states with open 4s or 4p subshell Cu-to Ge-like ions [8], which are partially summarized in table 1.…”
Section: Analysesmentioning
confidence: 99%
“…In slow collisions of multiply charged ions with He, single electron capture may be regarded as the dominant process with transfer ionisation making a significant contribution [5][6][7][8][9]. Therefore the final charge states in the production of Sn and Xe ions due to collisions of Sn q+ with He and Xe q+ with He are Sn (q-1)+ and Xe (q-1)+ respectively.…”
Section: Resultsmentioning
confidence: 99%